SISTEM PAKAR MENDIAGNOSA PENYAKIT CANINE DISTEMPER PADA ANJING MENGGUNAKAN METODE CERTAINTY FACTOR - Sitohang, Rirido Apriyanto; Fahmi, Hasanul (STMIK Kaputama, 2019)
Expert System in determining the type of disease in animals is very promising, but what needs to be watched is when the disease that attacks the animal is a malignant disease that even leads to death caused by viruses, weather changes, and how to care for these animals. The benefits of diagnosing diseases in animals are expected for animal lovers to be able to overcome animal diseases without having to go to PeetShop. Then we need an expert system in determining the disease using the certainty factor method because it is accurate, fast, and precise in diagnosing the disease in accordance with the symptoms of the disease.